BI 102 - General Biology 2 - Linn Benton Virtual College (2018)
This is an introductory lab science course intended for majors in disciplines other than the biological sciences. The topics presented include biological molecules, cellular biology, genetics and inheritance, biotechnology, and evolutionary processes. Additionally, the course is designed to help you discover the applications of science in your everyday life, as well as provide elements of critical thinking.